PENINGKATAN KETERAMPILAN TAJHIZ MAYIT MELALUI PENGGUNAAN LABORATORIUM PAI PADA SISWA KELAS XI IPA-1 SMA NEGERI 8 BANDA ACEH - Elvita Zamora (Jurnal Ilmiah Didaktika, 2017)
This research intended to know teachers’ activities to manage the learning process of tajhiz mayit by using the PAI laboratory; students’ activities in the tajhiz mayit by using the PAI laboratory; and the practical ability of students of class XI IPA-1 SMAN 8 Banda Aceh on tajhiz materials. This research is a Classroom Action Research (CAR) with four cycles, each consists of four stages: planning, implementation, observation, and reflection. The results of data analysis indicated that there wis an increase in the average value of students and their active participation in each subject matter, ranging from bathing, shrouding, doing prayer for, and burying the dead body. For example, teacher activity in managing learning process in the first cycle of first meeting on bathing the dead reached 64.28 in average falling into mild category; and at second meeting increased to 87.71 in average with good category. In the cycle II, on the first meeting on the subject of shrouding the dead body was 64.28 in average falling into mild category; and at the second meeting increased to 89.28 on average falling into a very good category. Likewise, the increase in the score average and students’ participations in other cycles after the use of CAR in the laboratory.